Women's Essence, Perception, and Premarital Education Case Study of Marriage Guidance at the KUA of Lohbener District - Sahmiatik, Elis; Rian Hidayat, Ario; Leany, Muhammad; Sulistio, Dody (RUSYDIAH: Jurnal Pemikiran Islam, 2024)
Artikel ini membahas bimbingan perkawinan yang diberikan kepada calon pengantin khususnya perempuan, dalam mempersiapkan peran sebagai istri dan ibu. Fokusnya pada materi bimbingan, kesiapan mental calon pengantin, serta persepsi perempuan terhadap esensi dan perannya setelah menikah. Penelitian ini menggunakan metode kualitatif dengan studi kasus di KUA Kecamatan Lohbener, melalui observasi partisipan, wawancara mendalam, dan dokumentasi. Temuan utama mencakup desain pendidikan pranikah memiliki materi yang meliputi strategi kesiapan mental menghadapi pernikahan dan pemahaman atas peran perempuan untuk mendewasakan usia menikah pertama. Meskipun materi yang diberikan mencakup aspek hukum, ekonomi, dan manajemen rumah tangga, namun belum menjangkau materi psikologis yang disampaikan oleh para ahli seperti psikolog.   This article discusses premarital counseling provided to prospective brides, particularly women, in preparing them for their roles as wives and mothers. The focus is on the counseling material, the mental readiness of brides-to-be, and women's perceptions of the essence and their roles after marriage. This research employs a qualitative method with a case study conducted at the Office of Religious Affairs (KUA) in Lohbener District, utilizing participant observation, in-depth interviews, and documentation. The key findings reveal that the design of premarital education includes material covering strategies for mental readiness in facing marriage and understanding women's roles in ensuring maturity at the time of their first marriage. Although the material addresses legal, economic, and household management aspects, it does not yet cover psychological topics delivered by experts such as psychologists.